LEAF LITTER AS A FOOD RESOURCE FOR RANGE LIVESTOCK - P. Rodriguez-Santillan; H. Bernal-Barragan; Ma. Cerrillo-Soto; H. Gonzalez-Rodriguez; A.S. Juarez-Reyes; Guerrero-Cervantes; R.G. Ramirez-Lozano (Journal of Animal and Plant Sciences, 2014)
Leaf litter samples from two undisturbed sites in the Tamaulipan Thornscrub vegetation at northeastern Mexico were evaluated monthly, during 2007, for chemical composition, true in vitro organic matter digestibility (IVOMD), in vitro gas production (IVGP, 24 h), metabolizable energy (ME) and microbial protein (MP), in absence or presence of polyethylene glycol (PEG). Neutral detergent fiber (organic matter; mean = 40.8%), acid detergent fiber (ADFom; 28.8%), lignin (20.2%), crude protein (CP; 11.5%), condensed tannins (CT; 0.6%), ether extract (EE; 2.9%) contents, and IVOMD (63.0%) values and the interactions site*month were different between sites and among months. Gas production without (53.2 ml/200mg) and with PEG (59.1), ME (9.9 and 10.9 MJ/kg, respectively) and MP values (11.5 and 13.8, µmol, respectively) were not different between sites, but were different among months. When leaf litter deposition was high (dry months; January-June) in both sites, NDF, lignin and CP were also higher than in other months. The in vitro gas production, ME and MP were higher with the addition of PEG compared with the samples without PEG. Moreover, MP content was higher during the wet months (July-September). Based on chemical composition and fermentation values, litter fall leaves have a high potential to be used as feed resource for range small ruminants.
Keywords: Chemical Composition; In Vitro Gas Production Parameters; Litter Fallen Leaves; Polyethylene Glycol; Tamaulipan Thornscrub Vegetation